Dự báo kết quả tác động của các chính sách lên một quần thể trong lý thuyết đổi mới - Lam, Le Xuan (Journal of Computer Science and Cybernetics, 2018)
On the prediction of impacting consequences policies on a population in the renewal theory. In the work one investigates quantitatively the consequences of policies impacting on a population in the renewal theory. The prediction of these consequences is translated to the solving a renewal equation and a value equation.